Design oriented failure model for wood accounting for different tensile and compressive behavior. (April 2015) - Blanco, C.; Cabrero, J.M.; Martin-Meizoso, A.; Gebremedhin, K.G.
Highlights: A new failure model for clear-spruce wood under biaxial plane stress is presented. Based on wood fracture, it accounts for different tensile and compressive failure. The mathematically simple model requires only uniaxial strength values as input. The proposed model is more accurate than other phenomenological failure models. Abstract: Recent biaxial experiments on clear-spruce wood allow to have a more complete understanding of fracture behavior of wood. An elliptic failure surface, like that of Tsai–Wu, has been previously proposed as a failure surface. Previous works in this area have shown the need for further developments. In this study a new failure model that accounts for existing different couplings and interactions in the longitudinal compressive and tensional domains is presented. The model is based on the fracture behavior of clear spruce wood and related experimental works. The model is more accurate compared to existing phenomenological models.